2020
DOI: 10.1016/j.earscirev.2020.103280
|View full text |Cite
|
Sign up to set email alerts
|

The latest Ordovician Hirnantian brachiopod faunas: New global insights

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 199 publications
3
51
0
Order By: Relevance
“…This fauna, which historically denotes the lower-middle Hirnantian (Harper et al 2014), occurs at the top of the Husbergøya Formation and continues a few metres into the overlying Langøyene Formation. In a recent review, however, Rong et al (2020) demonstrated that the Hirnantia Fauna is indeed diachronous, reaching into the M. persculptus Graptolite Zone in places. Our isotopic data support a late Hirnantian age for these strata.…”
Section: A2 Biostratigraphical Inference At Konglungø Based On Brachiopodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fauna, which historically denotes the lower-middle Hirnantian (Harper et al 2014), occurs at the top of the Husbergøya Formation and continues a few metres into the overlying Langøyene Formation. In a recent review, however, Rong et al (2020) demonstrated that the Hirnantia Fauna is indeed diachronous, reaching into the M. persculptus Graptolite Zone in places. Our isotopic data support a late Hirnantian age for these strata.…”
Section: A2 Biostratigraphical Inference At Konglungø Based On Brachiopodsmentioning
confidence: 99%
“…The Dalmanella Association occurs in the regressive facies immediately above the Hirnantia Association in the Langøyene Formation. According to Rong et al (2020), both the Cliftonia-Hindella and the Dalmanella associations developed in the Oslo-Asker district may represent a low-diversity Hirnantia Fauna. Lastly, the topmost strata of the Langøyene Formation contain the oolitic Pilodden Member.…”
mentioning
confidence: 99%
“…Based on a comprehensive dataset, Rong et al (2020a) recognized two successive Hirnantian evolutionary brachiopod faunas,: the Hirnantia Fauna and the succeeding Edgewood-Cathay Fauna. The former, widespread and diachronous, was related to the glacial acme in the early-mid Hirnantian, and the latter thrived during post-glacial, warmer, shallow-water carbonate and siliciclastic environments of low latitudes (e.g., Laurentia, Baltica, Kolyma, Central Asia, Siberia, and South China).…”
Section: Affinities Of the Belgian Hirnantia Fauna Assemblagementioning
confidence: 99%
“…The appearance, lifespan, composition, and geographical distribution of these survivor communities are essential to understand what triggered the extinction and how it happened. Recently, Rong et al (2020a) analyzed all the reported occurrences of brachiopod Hirnantian fossil assemblages and recognized two successive evolutionary faunas related to the first and second phases of the extinction: the Hirnantia Fauna sensu stricto, a widespread and diachronous community related to the glacial acme in the early-middle Hirnantian; and the newly named Edgewood-Cathay Fauna, adapted to the warmer waters of the late Hirnantian and early Rhuddanian (Silurian) post-glacial stage, occupying the low-latitude biotopes left vacant by the disappearance of the Hirnantia Fauna. *Corresponding author In Belgium, the occurrence of Hirnantian sequences was first postulated by Billiaert (2000) and Herbosch et al (2002) based on the presence of coarse terrigenous beds in the Génicot Formation of the Central Condroz Inlier, which was interpreted as the sedimentological expression of the Hirnantian glaciation sea level drop (Vanmeirhaeghe and Verniers, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation